DESIGN OF HOTEL PERFORMANCE LEVEL MEASUREMENT SYSTEM BASED ON HALAL VALUE WITH BSC METHOD - Hanin FItria; Syahrial Aman; Tita Latifah Ahmad (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2021)
In running the hotel business, it is always required to be able to compete and maintain the loyalty of the stakeholders in order to continue to exist. One of the efforts to be able to compete and maintain the loyalty of stakeholders is to find out how far the performance of the hospitality business is and what efforts are being made to improve its performance. In measuring company performance, it does not only focus on general aspects, but also considers other aspects, namely measuring company performance based on its halal value. In this study, the Balanced Scorecard method was used based on halal values ​​to be able to measure the company's performance. The results obtained after measuring using the Balanced Scorecard, namely the final score of the company's overall performance was obtained at 82.08% which was included in the very good category. From a financial perspective, the results of achievement, level of achievement, and scores from 2013 to 2015 were 32.95%, 71.04%, and 71.04%, respectively. Then from the customer's perspective, the results of achievement, level of achievement, and scores from 2013 to 2015 were 83.98%, 92.48%, and 92.48%, respectively. From the perspective of internal business processes, the results of achievement, level of achievement, and scores from 2013 to 2015 were 83.34%, 83.34%, and 83.34%, respectively. From the growth and learning perspective, the results of achievement, level of achievement, and scores from 2013 to 2015 were 60.78%, 86.26%, and 86.26%, respectively. However, the measurement using the Balanced Scorecard only focuses on the company's financial results and the unfavorable correlation between non-financial measures and the results. This situation will be a weakness of the Balanced Scorecard method because it cannot continue to take more specific steps forward so it cannot perform more accurate performance measurements.